Psychosocial Factors, Exercise Adherence, and Outcomes in Heart Failure Patients: Insights From Heart Failure. (November 2015) - Cooper, Lauren B.; Mentz, Robert J.; Sun, Jie-Lena; Schulte, Phillip J.; Fleg, Jerome L.; Cooper, Lawton S.; Piña, Ileana L.; Leifer, Eric S.; Kraus, William E.; Whellan, David J.; Keteyian, Steven J.; O'Connor, Christopher M.
Abstract : Background—: Psychosocial factors may influence adherence with exercise training for heart failure (HF) patients. We aimed to describe the association between social support and barriers to participation with exercise adherence and clinical outcomes. Methods and Results—: Of patients enrolled in Heart Failure: A Controlled Trial Investigating Outcomes of Exercise Training (HF-ACTION), 2279 (97.8%) completed surveys to assess social support and barriers to exercise, resulting in the perceived social support score (PSSS) and barriers to exercise score (BTES). Higher PSSS indicated higher levels of social support, whereas higher BTES indicated more barriers to exercise. Exercise time at 3 and 12 months correlated with PSSS ( r = 0.09 and r = 0.13, respectively) and BTES ( r =−0.11 and r =−0.12, respectively), with higher exercise time associated with higher PSSS and lower BTES (All P <0.005). For cardiovascular death or HF hospitalization, there was a significant interaction between the randomization group and BTES ( P =0.035), which corresponded to a borderline association between increasing BTES and cardiovascular death or HF hospitalization in the exercise group (hazard ratio 1.25, 95% confidence interval 0.99, 1.59), but no association in the usual care group (hazard ratio 0.83, 95% confidence interval 0.66, 1.06). Conclusions—: Poor social support and high barriers to exercise were associated with lower exercise time. PSSS did not impact the effect of exercise training on outcomes. However, for cardiovascular death or HF hospitalization, exercise training had a greater impact on patients with lower BTES. Given that exercise training improves outcomes in HF patients, assessment of perceived barriers may facilitate individualized approaches to implement exercise training therapy in clinical practice. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00047437. Abstract : Supplemental Digital Content is available in the text.